Effect of solvent extracted soybean meal and full-fat soya on the protein and amino acid digestibility and body amino acid composition in rainbow trout (Oncorhynchus mykiss) - Harlioglu, Ayse Gul (Iranian Fisheries Research Organization, 2012)
This study was carried out to investigate the apparent digestibility coefficients (ADCs) value of protein, amino acid and energy and body amino acid composition of rainbow trout fed solvent extracted soybean meal (SBM) and full-fat soybean meal (FFS) partly replacing fish meal (FM) in diets. Five iso nitrogenous (average 50.36% crude protein) and energetic (4294 kcal/kg total energy) diets were designed in 5 groups in triplicates. Diet one as control group with 43% FM and 25% SBM, Diet 2 with 28% FM and 40% SBM, Diet 3 with 13% FM and 55% SBM, Diet 4 with 28% FM and 40% FFS, Diet 5 with 13% FM and 55% FFS. Diets were fed to trout fishes with 49 g initial body weight for 20 weeks at 8.8 +/- 0.45 degrees C. It was found that ADCs of energy, protein and most amino acids particularly methionine and lysine and fish body muscle lysine levels, significantly decreased by increasing the amount of FFS and SBM in diets (P<0.05). On the other hand, valine, isoleucine, threonine, methionine, phenylalanine, lysine and histidine showed a decreasing tendency with the increasing proportion of SBM in fish body composition. It was concluded that increasing the SBM and FFS percent replacing FM in trout fish diet, caused reducing protein, amino acid and energy digestibility, compared with the control diet. However, it can also be concluded that the replacement of SBM was more efficient than the replacement of FFS as regarding growth, ADCs of protein and essential amino acid contents of O. mykiss.
Keywords: Rainbow trout; Oncorhynchus mykiss; Soybean meal; Full-fat soybean meal; Amino acid; Digestibility